NOx reduction studies on a diesel engine operating on waste plastic oil blend using selective catalytic reduction technique. Issue 2 (April 2019) - Ayodhya, Archit S.; Lamani, Venkatesh T.; Thirumoorthy, M.; Kumar, G.N.
Abstract: The constant escalation in the consumption of petroleum products has compelled researchers to discover for new alternative fuels which can be successfully incorporated in the existing automotive engines. Oil derived from waste plastics is one such alternative, which not only ensures longevity of fossil fuels but also assists in bringing down the hazardous impacts caused by the improper disposal of plastic wastes. This work focuses on the utilization of valuable energy of toxic non-biodegradable waste plastics to lucratively be used as an alternative fuel. An attempt was further made to reduce the NOX emissions which increased with the use of waste plastic oil blend. The main objective of this experimental investigation is to study the performance & emission characteristics of a twin cylinder CRDI engine subjected to selective catalytic reduction (SCR) after-treatment technique. Different flow rates of ammonia as a reducing agent were tested and concluded that a flow rate of 0.5 kg/hr furnishes optimum results. A comparison of NOX reduction efficiency was also made between SCR and EGR techniques. The comparison eventually indicated that SCR gives better NOX conversion efficiency at higher loads without any adverse effect on the engine performance while operating on Waste Plastic Oil blend (P30). Highlights: Performance, combustion and emission characteristic of waste plastic oil blend is investigated. Rhodium/ceramic catalyst is found to be very active in the medium temperature range of 240°C-280°C. SCR technique is observed to give getter NOx conversion efficiency at higher loads in comparison to EGR. 0.5 kg/hr ammonia flow rate furnished optimum results.